One-pot concurrent biosynthesis of biphasic CuxO (cuprous and cupric oxide) nanoparticles using leaf extract of Eichhornia crassipes and investigation of their potent healthcare applications - Moudgil, Aliesha; Varma, Sanjana; Shinde, Manish D.; Vamkudoth, Koteswara Rao; Sarkar, Dhiman M.; Shende, Rajnigandha A.; Amalnerkar, Dinesh; Chaudhari, Bhushan P. (Emergent Materials, 2022)
Eichhornia crassipes, an aquatic weed, has been used for the one-pot quick synthesis of cuprous and cupric oxide nanoparticles in this report. The identification and validation of the formed nanoparticles were successfully done by sophisticated characterization techniques such as UV–visible spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Their biomedical interventions were assessed by their antioxidant and anticancer activities. The synthesized nanoparticles have a spherical morphology with an average diameter of 10 nm. Antioxidant assay performed showed an increasing trend in a dose-dependent manner with the percentage radical scavenging activity up to 94.70% at a much higher concentration of 1000 µg/ml. The antioxidant potential at such higher concentration is suspected to invoke a change in the cytotoxic potential of the nanoparticles which is then verified by the MTT assay. A significant cytotoxic activity against HeLa (cervical cancer) and HCT 116 (colorectal carcinoma) cell lines was detected with noted IC50 values of 17.17 and 13.70 µg/ml respectively. The conclusive findings obtained are enough to substantiate the use of these nanoparticles in biomedical areas specifically in anticancer treatment due to their high toxicities. The hazards imposed by Eichhornia crassipes can be alleviated by using them as biofactories for the synthesis of a variety of nanomaterials. This helps in curbing the water pollution issues as well as the developing synthesis protocols for robust and stable nanoparticles.